The utilization of village-information system for integrated social welfare data management: actor-network theory approach in Gunungkidul regency - Elanto Wijoyono (Jurnal Teknosains, 2021)
As the main reference to poverty alleviation in Indonesia, the policy of integrated welfare data management by the Ministry of Social Affairs still contains many inaccuracies. This has an impact on beneficiary groups as the target of the implementation of national programs on poverty reduction. This study shows how Integrated Social Welfare Data management by the local government in Gunungkidul Regency, Special Region of Yogyakarta, can solve the inaccuracy. The analysis was conducted with qualitative methods, based on actor-network theory. Data collection, verification, and validation are processed by integrating Village Information System (SID BERDAYA) and Regency Information System (SIKAB) in Gunungkidul at the local level, with the Social Welfare Information System - Next Generation (SIKS-NG) by the Ministry of Social Affairs in national level. This integration is needed to improve the quality of data accuracy and validity. Strengthening the participation and transparency of social interaction between government agencies at every level (from the village level to the national level) and the community people are important since communities are the beneficiaries. These processes will develop a reflective scheme, to make sure the quality of planning and development program on poverty alleviation is running with accurate and valid data.